(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article analyzes the role of women historians in the historical science of the renewing Uzbekistan, their scholarly legacy, and their influence on the formation of historical consciousness. Based on sources, the article highlights the activities of women scholars-historians, archaeologists, literary scholars, and poets-who actively participated in the development of historical science from the Soviet period to the present day. The article demonstrates the possibilities of rethinking history from a gender perspective through scientific research, archaeological excavations, and artistic and historical images created by women. The article draws on dozens of scholarly sources and aims to reassess the role of women scholars in modern historiography